O afeto terceiro idade: a senexão como Instituto Jurídico aqdequado à colocação ou estabilização de idosos em família substituta - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The present article addresses the legislative proposals for the adoption of elderly people and Senexão as (in)adequate institutes for the placement or stabilization of elderly people in substitute families. The analysis is developed within the scope of Family Law, in fundamental correlation with the Law of the Rights of Older Persons, from a socio-affective perspective of later life, while taking into account the specificities involved in the legal protection of this vulnerable group. The study seeks to answer the following research question: which legal institute is most appropriate for the placement or stabilization of older persons in substitute families? The general objective is to demonstrate that, between adoption and Senexão, Senexão emerges as the legal institute more suitable for the placement or stabilization of older persons in substitute families. The research is guided by specific objectives of a descriptive, exploratory, and explanatory nature, namely: a) to discuss the importance of active family presence in later life; b) to present the challenges imposed on Family Law and the Law of the Rights of Older Persons by population aging; c) to identify family coexistence as a legally protected interest within the Brazilian legal system; d) to reflect on the placement of older persons in substitute families as a means of ensuring their fundamental right to family life; e) to examine the legal institute of adoption and the legislative proposals related to the adoption of older persons; f) to assess whether adoption is adequate for the placement or stabilization of older persons in substitute families; g) to analyze the legal institute of Senexão; and h) to evaluate whether Senexão is adequate for the placement or stabilization of older persons in substitute families. To achieve these objectives, the research employs the deductive method, a qualitative approach, and bibliographic and documentary research techniques. This paper demonstrated the duty of the researchers to contribute to discussions which aimed to strengthen the constitutional rights of the elderly - and, specifically, the right of the elderly to family life, considering the aging rates of the Brazilian population and the growing institutionalization of people at this age group. As a result, it was found that between Adoption and Senexão, it is the legal institute of Senexão that emerges as a suitable institute for the placement or stabilization of elderly people in substitute families, taking account the peculiarities that are related to the attempt to regulate the emotional support of elderly people and the possibility of expanding the conceptual spectrum of socio-affectivity for the formation of family ties. However, it was identified that the law project that aims to implement Senexão still needs improvements.
Affection in old age: the legal concept of "senexão" as an appropriate legal institution for placing or stabilizing elderly people in substitute families
Keywords: Adoção de idosos; Direito das familias; Direito das pessoa; Elderly adoption; Family law; Rights of the elderly person; CIENCIAS SOCIAIS APLICADAS